صفة السرية الخاصة بالمعلومات الداخلية في سوق الأوراق المالية وفقاً للقانون السوري - قرباش, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس هذا البحث صفة السرية التي ترتبط بالمعلومات الداخلية في سوق الأوراق المالية من حيث أنَّ المعلومات الداخلية هي معلومات جوهرية مؤثرة في السوق ومع توافر صفة السرية فيها تُصبح قابلة للاستغلال من قِبَل الفئة المُطَّلعة عليها. ويقوم البحث بدراسة صفة السرية الخاصة بالمعلومات الداخلية عبر البحث في مفهومها وإيضاح تفاصيله, وفي أسلوب اعتماد المشرع لهذه الصفة حتى تتم شروط المعلومات الداخلية في سوق الأوراق المالية ومدى توفيقه بتشريع القواعد الخاصة بهذه الصفة, لنصل في نهاية البحث إلى مجموعة من النتائج والتوصيات. ومن أهم النتائج التي توصَّلنا إليها: ضرورة تمييز القانون بنص صريح للفرق بين صفة السرية الخاصة بالمعلومات الداخلية وبين المعلومات السرية التي لايجب الإفصاح عنها, وضرورة اشتراط صفة السرية بشكل صريح في نص القانون المتعلِّق بالمعلومات الداخلية, وضرورة ربط فقدان صفة السرية الخاصة بالمعلومات الداخلية بالإفصاح الرسمي والعام والكامل عن المعلومات الداخلية وذلك بنصٍّ صريح في القانون. The research studies the confidentiality attribute which correlates with inside information in the securities exchange. Inside information is essential substantive information in the market and since it is confidential, it becomes profitable for insiders. Also the research studies the confidentiality attribute of inside information by researching in its form and showing its details, and by researching in the way the legislator adapts it to complete all its conditions in the securities exchange. Then, we reach a group of results and recommendations. From the most important results which we have reached are the following: It's necessary to overtly distinguish between the confidentiality attribute of inside information and the confidential information which mustn't be revealed. It's also necessary to stipulate the confidentiality attribute of inside information overtly in law codes, and to relate losing the confidentiality attribute of inside information to the official, public and complete declaration in a frank item of law.